The Role of PPAR Gamma in Systemic Sclerosis - Andréa Tavares Dantas; Michelly Cristiny Pereira; Moacyr Jesus Barreto de Melo Rego; Laurindo Ferreira da Rocha; Ivan da Rocha Pitta; Cláudia Diniz Lopes Marques; Angela Luzia Branco Pinto Duarte; Maira Galdino da Rocha Pitta (PPAR Research)
Fibrosis is recognized as an important feature of many chronic diseases, such as systemic sclerosis (SSc), an autoimmune disease of unknown etiology, characterized by immune dysregulation and vascular injury, followed by progressive fibrosis affecting the skin and multiple internal organs. SSc has a poor prognosis because no therapy has been shown to reverse or arrest the progression of fibrosis, representing a major unmet medical need. Recently, antifibrotic effects of PPARγ ligands have been studied in vitro and in vivo and some theories have emerged leading to new insights. Aberrant PPARγ function seems to be implicated in pathological fibrosis in the skin and lungs. This antifibrotic effect is mainly related to the inhibition of TGF-β/Smad signal transduction but other pathways can be involved. This review focused on recent studies that identified PPARγ as an important novel pathway with critical roles in regulating connective tissue homeostasis, with emphasis on skin and lung fibrosis and its role on systemic sclerosis.